The Purpose And Benefits Of Life Insurance (Journal of Pharmaceutical Negative Results, 2023)
Life Insurance can be defined as a contract between an insurance policy holder and an insurance company, where the insurer promises to pay a sum of money in exchange for a premium, upon the death of an insured person or after a set period .The research method followed is descriptive research. The data is collected through a questionnaire and the sample size is 200.Convenience sampling method is adopted in the study to collect the data. The samples were collected from the general public with special reference to Chennai region. The independent variables are age , gender, income level and education level of respondents. The dependent variables are do you think that life insurance is concerned with burden of proof ,do you think that which is the disadvantage of life insurance,purpose makeup for losses of earnings,purpose for payment of medical expenses.The researcher used graphs to analyze the data collected.the findings of the study is that rural people were not aware about insurance policies so the government should take initiatives to make rural people aware about the benefits of life insurance and help them to take insurance policies.